1995
DOI: 10.2307/1941678
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variation in Abundance

Abstract: To quantify the magnitude and pattern of spatial variation in local population density within a single species, we analyzed large numbers of samples, representing a large geographic area or a wide range of ecological conditions. Our analyses focused on, but were not limited to, censuses of birds recorded in the North American Breeding Bird Survey. Birds and other organisms exhibited a common pattern: each species was represented by only a few individuals in most of the sample sites where it occurred, but was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

33
600
9
17

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 652 publications
(659 citation statements)
references
References 21 publications
33
600
9
17
Order By: Relevance
“…As many theoretical and empirical 416 studies have observed, identifying patterns and processes 417 of temporal population dynamics is not an easy task and 418 it is necessary to consider also the effect of random 419 events, like environmental and demographic stochastic-420 ity (Brown et al 1995;Ives and Klopfer 1997). Even the 421 lakes that received wastewater can dry in summer if the 422 water accumulated in winter was low.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…As many theoretical and empirical 416 studies have observed, identifying patterns and processes 417 of temporal population dynamics is not an easy task and 418 it is necessary to consider also the effect of random 419 events, like environmental and demographic stochastic-420 ity (Brown et al 1995;Ives and Klopfer 1997). Even the 421 lakes that received wastewater can dry in summer if the 422 water accumulated in winter was low.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…One of the principal goals of ecology is to understand the processes and mechanisms that control the distribution, abundance and coexistence of species [1,2]. Classical theoretical ecology predicts that two species competing for the same resources cannot stably coexist (the exclusion principle by Gause [3]).…”
Section: Introductionmentioning
confidence: 99%
“…El estudio de la distribución de especies de acuerdo con categorías de abundancia, además de indagar acerca de los efectos del tamaño de la muestra, busca explicar si la relación de éstas con su medioambiente, está reflejada en la distribución de las abundancias relativas (Brown et al 1995;Alonso et al 2008). En otras palabras, pretende indagar acerca de la diferencia adaptativa que supone ventajas competitivas de algunas especies respecto al uso de los recursos en un hábitat determinado (Preston 1962;Tilman y Pacala 1993;Brown et al 1995).…”
Section: Introductionunclassified
“…En otras palabras, pretende indagar acerca de la diferencia adaptativa que supone ventajas competitivas de algunas especies respecto al uso de los recursos en un hábitat determinado (Preston 1962;Tilman y Pacala 1993;Brown et al 1995). Según Preston (1962), las especies de abundancia intermedia pueden ser especialmente útiles como indicadores diferenciales de la adaptación al nicho.…”
Section: Introductionunclassified